La Constantin : Celebrated Crimes - Dumas, Alexandre, 1802-1870 (Salt Lake City, UT : Project Gutenberg, 2004)
"La Constantin" by Alexandre Dumas is a historical novel likely written during the late 19th century. The narrative unfolds in 17th-century Paris, offering a glimpse into the intrigues, moral complexities, and personal stories of its characters amidst the backdrop of societal upheaval and corruption. The story primarily revolves around Marie Leroux, the widow of Jacques Constantin, and the enigmatic figure of the Chevalier de Moranges, embroiled in tangled relationships and hidden identities. At the start of the novel, the reader is introduced to a smoke-filled tavern where three gentlemen engage in lighthearted banter and the suggestion of an audacious scheme. Among them is Commander de Jars, who jokes about his young companion, the Chevalier de Moranges, while the king's treasurer tries to pry into de Jars' past and secrets. The setting quickly transitions to focus on the troubled past of Angelique-Louise de Guerchi, a former maid of honor now living in obscurity and seeking redemption amidst her crumbling reputation. As the narrative unfolds, various characters converge, each with their own secrets and motives, leading to themes of love, jealousy, and vengeance that promise to intertwine their fates dramatically. (This is an automatically generated summary.)
Release date is 2004-09-22
Produced by David Widger
Keywords: Crime